Changes in food reward and intuitive eating after weight loss and maintenance in former athletes with overweight or obesity. Issue 5 (28th March 2022) - Nunes, Catarina L.; Carraça, Eliana V.; Jesus, Filipe; Finlayson, Graham; Francisco, Rúben; Silva, Marlene N.; Santos, Inês; Bosy‐Westphal, Anja; Martins, Paulo; Minderico, Cláudia; Sardinha, Luís B.; Silva, Analiza M.
Abstract: Objective: This study aimed to explore the following: 1) the impact of Champ4Life's intervention on intuitive eating and food reward; and 2) associations between changes in eating behavior and changes in body composition. Methods: A total of 94 former athletes (mean [SD], BMI = 31.1 [4.3] kg/m 2, age = 43.0 [9.4] years, 34% female) assigned to intervention ( n = 49) and control groups ( n = 45) underwent 4 months of active weight loss (WL) followed by 8 months of WL maintenance. Intuitive eating and food reward were assessed by the Intuitive Eating Scale and the Leeds Food Preference Questionnaire, respectively. Results: The WL was −4.8% (4.9%) and 0.3% (2.6%) for the intervention and control groups, respectively. Participants reported a decrease in fat bias for explicit/implicit wanting and explicit liking after 4 months and 1 year. For intuitive eating, the unconditional permission to eat decreased after 4 months, and the body–food choice congruence increased after 1 year. Changes in unconditional permission to eat and in body–food choice congruence were positively and negatively associated with both Δweight and with Δfat mass, respectively. Changes in explicit wanting for fat and taste bias were associated with Δweight. Conclusions: Food reward decreased after a moderate WL intervention. Participants successfully maintained their reduced weight, and most of the changes in eating behavior remained significant at the end of the follow‐up period. Lifestyle interventions aiming at WL should also consider intuitive eating and food reward.